The Relationship Between Socioeconomic and Dietary Patterns with Nutritional Status in 10th Grade Adolescents of MAN 1 Samarinda - Damarti Sam, Dela; Titania, Titania; Adisa Mahendra Putri, Diera; Marcello Putra Hardani, Iqbal; Devyana Putri Tobing, Melisa; Tia Rahmadani, Aulia; Dia Gutami, Anggie; Triana Tambunan, Syebat; Sinta Aulia Safariana, Nadia; Nur Azizah, Mirsa (Mulawarman International Conference on Tropical Public Health, 2025)
Adolescent health can be influenced by diet and supported by social and economic factors. Good nutritional status will affect learning achievement, productivity, and the overall quality of life of adolescents. Adolescent health is strongly influenced by a healthy diet and is linked to socioeconomic support factors in adolescents. According to the Ministry of Health, the adolescent age group starts from the age of 10 years to less than 18 years. Indicators of nutritional status assessment in healthy adolescents can be characterized by weight, height, and Body Mass Index. The Objective aims to analyze the relationship between socioeconomic status and diet with the nutritional status of 10th grade adolescents at MAN 1 Samarinda. This research was conducted on October 3, 2024. The population in this study were 10th grade adolescents at MAN 1 Samarinda with a total of 85 subjects. The research design used was analytic observational with a quantitative approach. The method used is Cross Sectional. The research instruments or tools used in this study were questionnaires and anthropometric measurements, namely body weight and height to determine BMI. The results of the bivariate analysis using the Chi-Square test showed that socioeconomic status represented by respondents' daily allowance, when associated with Body Mass Index resulted in a Pvalue of 0.556 > α (0.05). Meanwhile, eating behavior represented by respondents' breakfast habits, when associated with Body Mass Index resulted in a P-value of 0.039 < α (0.05). Based on the research conducted, it shows that there is a relationship between socioeconomic status and diet with body mass index which is related to breakfast with body mass index. So, it is expected to provide insight to students and parents on the importance of breakfast in order to improve the quality of life of students. When students have a body mass index that is less, it will certainly affect the spirit, as well as student achievement at school and in the future.